Rabbit Neutering: The open technique unveiled - Rashid, Mursaleen; Dar, Shahid Hussain; Ahmad, Raja Aijaz; Gugjoo, Mudasir Bashir; Athar, Hakim; Shafi, Alisa; Rather, Shakir Ahmad (Indian Journal of Veterinary Surgery, 2026)
-